GABA Withdrawal Modifies Network Activity in Cultured Hippocampal Neurons - H. Golan; K. Mikenberg; V. Greenberger; M. Segal (Neural Plasticity)
Dissociated hippocampal neurons, grown in culture for 2 to 3 weeks, tended to fire bursts of synaptic currents at fairly regular intervals, representing network activity. A brief exposure of cultured neurons to GABA caused a total suppression of the spontaneous network activity. Following a washout of GABA, the activity was no longer clustered in bursts and instead, the cells fired at a high rate tonic manner. The effect of removing GABA could be seen as long as 1 to 2 days after GABA withdrawal and is expressed as an increase in the number of active cells in a network, as well as in their firing rates. Such striking effects of GABA removal may underlie part of the GABA withdrawal syndrome seen elsewhere.